Aesthetic and functional outcomes in patients with a nasal prosthesis. Issue 11 (November 2017) - Becker, C.; Becker, A.M.; Dahlem, K.K.K.; Offergeld, C.; Pfeiffer, J.
Abstract: The aim was to evaluate the aesthetic and functional outcomes in patients with a nasal prosthesis after radical tumour resection. A questionnaire with 15 domains was created to evaluate the satisfaction of patients with their nasal prosthesis. Correlations with the results of the University of Washington Quality of Life (UWQOL) questionnaire, which was also completed by the patients, were analyzed. Forty-three patients with a partial or total nasal prosthesis completed the questionnaire. Twenty-seven patients were male and 16 were female; their median age was 62 years. The median follow-up time after tumour resection was 33 months. The best result was obtained for overall function (85.5) and the worst result for nasal crusts (58.5). The average daily duration of prosthesis use was 17.4 h. There were sex-dependent and age-dependent differences in the domain 'self-confidence', age-dependent differences in the domain 'stability during sporting activities', and differences in the domain 'nose bleed' depending on the time since tumour resection. All patients would recommend this rehabilitation after rhinectomy. 'Satisfaction with function' had the most influence on UWQOL domains. The nasal prosthesis is a well-accepted rehabilitation after rhinectomy. The results for appearance are comparable to those obtained for nasal reconstruction, and high scores were found for the functional domains.